Rapid mangrove expansion triggered by low river discharge episode in Nanliu river estuary, Beibu Gulf of China - Liu, Tao; Huang, Rongyong; Sun, Yonggen; Liu, Ying; Song, Zhiguang (Frontiers in Marine Science, 2024)
Mangrove forest is critical primary producer, biological habitat and carbon sink in subtropicaltropical coast zone, the natural variation of mangrove coverage deserves study for a better understanding in the dynamics of mangrove coastal evolution. In this study, multispectral Landsat images since 1985 to 2018 are used to reconstruct the change in the coverage of mangrove (dominant specie is Aegiceras corniculatum) and salt marsh (dominant specie is Cyperus malaccensis) in Nanliu River estuary. Tidal flat elevation measuring and 210 Pb dating are used to study the substrate elevation when mangrove firstly colonizing salt marsh. Historical temperature record, river discharge record and the time series N/P concentration in sediment are analyzed. It is found that the mangrove forests have expanded rapidly in salt marsh since mid-1980s. The change in factors such as accommodation space, cold events frequency and nutrient supply can not explain the starting of mangrove expansion. A low river discharge episode lasting for 8 years since 1986 is considered to trigger the mangrove expansion in this area, as salt marsh plant died due to germination restriction caused by high salinity and mangroves colonized salt marsh habitat during this period. This case proves again that estuarine wetlands is very sensitive to salinity variation.